Legitimate Expectations in Administrative Procedure - Milkov, Dragan; Radošević, Ratko S. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The principle of legitimate expectations is one of the new principles of Serbian administrative procedure. Unfortunately, it is regulated in a very wage and imprecise manner. This is why the authors have tried to determine its true meaning. They have also posed the following question: is the principle of legitimate expectations necessary in Serbian administrative procedure? In reply to this question, they have confirmed their basic hypothesis and concluded that the answer is: no. This “principle” is just another way to name and explain some other principles – such as legality, equality and legal certainty. Legitimate expectations are just a reflection of these principles; they do not form some new and special principle. In Serbian administrative procedure, they change nothing and mean nothing.
Keywords: Administrative procedure, basic principles of administrative procedure, legitimate expectations.